Yield and quality of maize stover: Variation among cultivars and effects of N fertilization - Ming-yuan LIANG; Gui-yan WANG; Wei-li LIANG; Peng-fei SHI; Jing DANG; Peng SUI; Chun-sheng HU (Journal of Integrative Agriculture)
Biomass yields and concentrations of crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), acid detergent fiber (ADF), and crude fiber (CF) were analyzed for five cultivars of summer-sown maize (Zea mays L.) stover grown in field trials at three rates of N fertilization, and sampled immediately after grain harvest. The results revealed differences in yields and concentrations of nutrients according to stalk height and hence harvest portion among the cultivars. N application greatly increased biomass yield and CP, especially in upper stalks and to a lesser extent, EE. Concentrations of NDF and ADF decreased as N rate increased. The results show that stovers from all local popular maize cultivars are suitable as animal fodder and that moderate N application improves feed quality of stover.